PENGARUH SOCIAL MEDIA MARKETING, TERHADAP BRAND AWARENESS, BRAND IMAGE DAN REPURCHASE INTENTION DI KOPITIAM SURABAYA - Nur Aini Madjid; Joaquin Levi Toreh; Agustinus Nugroho (ITB AAS Indonesia Surakarta, 2026)
The food and beverage industry in Indonesia, particularly in the restaurant and cafe segment, is experiencing rapid growth, including the emergence of modern kopitiams in Surabaya. This study aims to examine and analyze the influence of social media marketing on brand awareness, brand image, and repurchase intention, while also exploring the mediating roles of brand awareness and brand image. Using an explanatory quantitative design, data were collected via Google Form questionnaires from 160 respondents in Surabaya, aged 17–27, who are active social media users and have visited a modern kopitiam at least twice. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The structural model (inner model) shows that social media marketing significantly influences brand awareness (t=4.713, p=0.000) and brand image (t=5.700, p= 0.000). Furthermore, brand image (t= 4.236, p=0.000) and brand awareness (t= 1.815, p=0.035) both have a positive and significant impact on repurchase intention. The R-Square values indicate that the model explains 23.2% of brand awareness, 21.6% of brand image, and 37.8% of repurchase intention. Both brand awareness and brand image were proven to serve as partial mediators in the relationship between social media marketing and repurchase intention. These findings suggest that consistent digital engagement and a strong brand identity are essential for driving customer loyalty in Surabaya's competitive culinary industry.